Mechanism of Trypanosoma cruzi Placenta Invasion and Infection: The Use of Human Chorionic Villi Explants - Ricardo E. Fretes; Ulrike Kemmerling (Journal of Tropical Medicine)
Congenital Chagas disease, a neglected tropical disease, endemic in Latin America, is associated with premature labor and miscarriage. During vertical transmission the parasite Trypanosoma cruzi (T. cruzi) crosses the placental barrier. However, the exact mechanism of the placental infection remains unclear. We review the congenital transmission of T. cruzi, particularly the role of possible local placental factors that contribute to the vertical transmission of the parasite. Additionally, we analyze the different methods available for studying the congenital transmission of the parasite. In that context, the ex vivo infection with T. cruzi trypomastigotes of human placental chorionic villi constitutes an excellent tool for studying parasite infection strategies as well as possible local antiparasitic mechanisms.